2021
DOI: 10.1108/cdi-09-2020-0233
|View full text |Cite
|
Sign up to set email alerts
|

Reverse mentoring, job crafting and work-outcomes: the mediating role of work engagement

Abstract: PurposeReverse mentoring and job crafting are innovative, employee-driven job resources that can lead to positive organizational outcomes. The purpose of this paper is to explore the role of work engagement in mediating the association of these resources with work performance and work withdrawal behavior.Design/methodology/approachHypotheses were tested using structural equation modeling on data obtained from 369 software developers in India.FindingsFindings demonstrate that reverse mentoring and job crafting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 76 publications
(86 reference statements)
2
29
0
Order By: Relevance
“…These characteristics exhibited by engaged employees make them higher performers at work (Bakker, 2009). Literature also evidence the positive association of work engagement with different forms of performance such as job performance, in-role and extra-role performance under different settings (Alessandri et al, 2018;Bakker et al, 2004;Halbesleben and Wheeler, 2008;Yalabik et al, 2013;Mäkikangas et al, 2016;Meyers et al, 2019;Rai et al, 2018;Van Wingerden et al, 2018) as well as work performance under similar settings (Garg et al, 2018). Work withdrawal behaviors, on the other hand, reflects the adverse behaviors (psychological and physical) exhibited by employees either to neglect work or to reduce the time invested on work, without compromising on their work-role.…”
Section: Outcomes Of Work Engagement Work Outcomesmentioning
confidence: 94%
See 1 more Smart Citation
“…These characteristics exhibited by engaged employees make them higher performers at work (Bakker, 2009). Literature also evidence the positive association of work engagement with different forms of performance such as job performance, in-role and extra-role performance under different settings (Alessandri et al, 2018;Bakker et al, 2004;Halbesleben and Wheeler, 2008;Yalabik et al, 2013;Mäkikangas et al, 2016;Meyers et al, 2019;Rai et al, 2018;Van Wingerden et al, 2018) as well as work performance under similar settings (Garg et al, 2018). Work withdrawal behaviors, on the other hand, reflects the adverse behaviors (psychological and physical) exhibited by employees either to neglect work or to reduce the time invested on work, without compromising on their work-role.…”
Section: Outcomes Of Work Engagement Work Outcomesmentioning
confidence: 94%
“…Work withdrawal behaviors, on the other hand, reflects the adverse behaviors (psychological and physical) exhibited by employees either to neglect work or to reduce the time invested on work, without compromising on their work-role. Engagement is found to be negatively related with absenteeism (which is an intensified form of withdrawal behavior) (Magee et al, 2017) and work withdrawal behavior (Garg et al, 2018). It has been reported that employees with high levels of engagement would cease to indulge in withdrawal behaviors and instead would proactively invest their maximal efforts toward the accomplishment of organizational goals (Zeijen et al, 2018).…”
Section: Outcomes Of Work Engagement Work Outcomesmentioning
confidence: 99%
“…The work engagement was researched vividly with multiple human resource conceptual frames as the Kahn's (2013) engagement and disengagements, new versions of 'Maslach Burnout Inventory-MBI' items, the grounded theories of 'individuals' expression of themselves' in the work atmosphere and other recent theories of Employee Involvement. The three psychological theories as Conservation of Resources Theory, the Social Cognitive Theory, and the Broaden-and-Build Theory were served to better understand the engagement of the workers in their job (Garg, Murphy, & Singh, 2021;Kahn & Heaphy, 2013;Maslach, & Leiter, 2017;Schaufeli et al, 2002). The Utrecht Work Engagement Scale (UWES) of Wilmar Schaufeli and Bakker which undergone multiple revisions was constructed on three engagement elements-vigour, dedication, and absorption-the extend of which found to reduces the burnout elements-exhaustion, inefficiency and cynicism-in the workers (Dimitriadou, Lavidas, Karalis, & Ravanis, 2021;Schaufeli et al, 2002).…”
Section: Relevant Literature a Work Engagementmentioning
confidence: 99%
“…Reverse Mentoring was measured using the eleven-item scale developed for a larger study (Garg et al, 2021). Sample items included "I feel competent in the content that I share with my mentee (senior)" and "My mentee (senior) values the ideas and suggestions that I offer".…”
Section: Methodsmentioning
confidence: 99%
“…The JD-R model provides the framework through which job resources (antecedents) influence individual and organizational outcomes through work engagement as a mediator (Schaufeli and Taris, 2014). Merging SET with JD-R further explains the mechanism behind this framework (Garg et al, 2021). As per SET, when the organization provides employees with job resources (such as social support, autonomy), they feel valued, and hence, they feel obliged to reciprocate toward the organization in the form of increased work engagement and consequently, improved outcomes (Saks, 2006).…”
Section: 33mentioning
confidence: 99%